Escherichia coli α-Hemolysin Triggers Shrinkage of Erythrocytes via K(Ca)3.1 and TMEM16A Channels with Subsequent Phosphatidylserine Exposure - Skals, Marianne (American Society for Biochemistry and Molecular Biology, 2010)
α-Hemolysin from Escherichia coli (HlyA) readily lyse erythrocytes from various species. We have recently demonstrated that this pore-forming toxin provokes distinct shrinkage and crenation before it finally leads to swelling and lysis of erythrocytes. The present study documents the underlying mechanism for this severe volume reduction. We show that HlyA-induced shrinkage and crenation of human erythrocytes occur subsequent to a significant rise in [Ca(2+)](i). The Ca(2+)-activated K(+) channel K(Ca)3.1 (or Gardos channel) is essential for the initial shrinkage, because both clotrimazole and TRAM-34 prevent the shrinkage and potentiate hemolysis produced by HlyA. Notably, the recently described Ca(2+)-activated Cl(−) channel TMEM16A contributes substantially to HlyA-induced cell volume reduction. Erythrocytes isolated from TMEM16A(−/−) mice showed significantly attenuated crenation and increased lysis compared with controls. Additionally, we found that HlyA leads to acute exposure of phosphatidylserine in the outer leaflet of the plasma membrane. This exposure was considerably reduced by K(Ca)3.1 antagonists. In conclusion, this study shows that HlyA triggers acute erythrocyte shrinkage, which depends on Ca(2+)-activated efflux of K(+) via K(Ca)3.1 and Cl(−) via TMEM16A, with subsequent phosphatidylserine exposure. This mechanism might potentially allow HlyA-damaged erythrocytes to be removed from the bloodstream by macrophages and thereby reduce the risk of intravascular hemolysis.